Sri Lanka from dominion to republic - Jacob, Lucy M. (Delhi, 1973)
The book was still in the press a new constitution declaring Ceylon the Republic of Sri Lanka was promulgated. Hence both the names - Ceylon and Sri Lanka- have been used interchangeably. This book attempts to unfold various aspects of Ceylone's relations with the UK since her independence in 1948. Providing a historical setting against which Ceylon's relations with the UK should be analyses, the study highlights the motivation underlying Colombo's relations with White Hall under the UNP regime.
Keywords: International relations